(untitled) (Journal of Parents and Teachers, 2025)
W. Barbe’s theory of the three learning channels (visual, auditory and kinesthetic) is presented. Each student has a different channel for receiving information, although classrooms prioritise the auditory channel, leaving less space for the visual and manipulative channels. The "Barbe Test" helps to identify each student’s dominant channel through different activities. To achieve more comprehensive and equitable learning, it is proposed that teachers adapt their teaching to include all three channels.